Filling the Gap for Obsessive-Compulsive Disorder Services in Canada: Implementing an Intensive Care Program. Issue 1 (January 2020) - Taube-Schiff, Marlene; Rector, Neil A.; Young, Rebecca; Larkin, Persephone; Richter, Margaret A.
Abstract : Abstract: Obsessive-compulsive disorder (OCD) is a significant psychiatric illness that can impact an individual in terms of their quality of life, functional abilities, and interpersonal relationships. Until recently, services for individuals with severe symptoms of OCD were limited within Canada. The Frederick W. Thompson Anxiety Disorders Centre at Sunnybrook Health Sciences Centre in Toronto, Canada, recently launched an intensive services program for individuals with severe symptoms of OCD. This article provides an overview of the steps that were taken to develop this program. Methods involved incorporation of information gathered from both service users and service providers of these models of treatment within North America and beyond. This article provides a potential treatment model for residential psychiatric treatment that can be applied to OCD and possibly other severe treatment refractory psychiatric illnesses in terms of methods used and generalizable key ingredients.